NSAID-Induced Adverse Drug Reaction: Mechanism and Management - Katherine A.Tjenggal; Rano K. Sinuraya; Cherry Rahayu; Rizky Abdulah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) are drugs to reduce pain or swelling. The use of these drugsin high doses or long-term can cause side effects or hypersensitivity problems, also known as Adverse DrugReaction (ADR). A literature review was carried out using the PubMed database by inserting the keywords‘NSAID’, ‘adverse drug reaction’, and ‘hypersensitivity’. All studies related to NSAIDs and their adversedrug reactions were included in this review, while genetic or pharmacogenomics studies and NSAIDs’effectiveness were excluded. The results showed that gastrointestinal (GI) problems such as duodenal ulcersor erosive gastritis are the most common diclofenac effects (2.05%). Cardiovascular issues, such as acutemyocardial infarction, were mostly caused by rofecoxib (2.12%). Hypersensitivity, both respiratory andskin, is commonly caused by ibuprofen with prevalence 50% and 67%, respectively. The most frequentkidney problem related to NSAIDs use is acute kidney injury. In comparison, the common hypersensitivityproblems are asthma, urticaria, and angioedema. Adverse drug reactions can be prevented or treated bylowering the dose, reducing the duration of treatment, adding companion drugs, or changing the type ofNSAID. In conclusion, it can be seen that ibuprofen severely caused kidney problems and hypersensitivity.On the other hand, diclofenac caused digestive issues, and rofecoxib caused cardiovascular problems.